2006
DOI: 10.1124/jpet.106.101881
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Arrhythmia Risk of the Antibacterials Moxifloxacin, Erythromycin, and Telithromycin Based on Analysis of Monophasic Action Potential Duration Alternans and Cardiac Instability

Abstract: Antibacterial drugs are known to have varying degrees of cardiovascular liability associated with QT prolongation that can lead to the ventricular arrhythmia torsade de pointes. The purpose of these studies was to compare the assessment for the arrhythmogenic risk of moxifloxacin, erythromycin, and telithromycin. Each drug caused dose-dependent inhibition of the rapidly activating delayed rectifier potassium current encoded by the human ether-á -go-go-related gene (hERG) with IC 20 concentrations of 31 M (moxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…First, several reports of arrhythmias associated with use of either oral or intravenous (IV) EES have been reported [17][18][19]. Second, in 2004, a large cohort study of Tennessee Medicaid patients from 1988 to 1993 showed a possible association between EES with a risk of sudden cardiac death through its extensive metabolism by the cytochrome P-450 3A isoenzymes [17].…”
Section: Introductionmentioning
confidence: 97%
“…First, several reports of arrhythmias associated with use of either oral or intravenous (IV) EES have been reported [17][18][19]. Second, in 2004, a large cohort study of Tennessee Medicaid patients from 1988 to 1993 showed a possible association between EES with a risk of sudden cardiac death through its extensive metabolism by the cytochrome P-450 3A isoenzymes [17].…”
Section: Introductionmentioning
confidence: 97%
“…In monophasic AP recordings from anesthetized guinea-pigs, erythromycin has been observed to increase both AP duration and alternans [Wisialowski et al 2006]. The drug has also been shown to increase AP duration in a concentration dependent fashion in rabbit Purkinje fibers and to prolong both QT interval and T peak T end in a concentration-dependent fashion in an arterial perfused rabbit left ventricular wedge preparation [Lu et al 2007].…”
Section: Pharmacodynamicsmentioning
confidence: 98%
“…Volberg and colleagues reported I hERG inhibition in a mammalian cell expression system by erythromycin with a half maximal inhibitory concentration (IC 50 ) of 72.2 mM, whilst in the same study its metabolite desmethyl-erythromycin also produced weaker I hERG inhibition (IC 50 of 147.1 mM). Some subsequent studies have reported lower I hERG block IC 50 values for erythromycin of 38.9 mM [Stanat et al 2003], 59.3 mM [Duncan et al 2006], and 21 mM [Wisialowski et al 2006].…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…There have been reports of erythromycin being associated with serious cardiac arrhythmias and prolonged QTc [38][39][40] . Erythromycin should not be used concurrently with medications metabolized by cytochrome P450 3A4 (CYP3A4) such as cisapride, terfenadine, pimozide, or astemizole as it is a CYP3A4 inhibitor.…”
Section: Motilin Agonists Erythromycinmentioning
confidence: 98%